Dexamethasone Protects Against Apoptotic Cell Death of Cisplatin-exposed Auditory Hair Cells In Vitro. Issue 9 (October 2015) - Dinh, Christine T.; Chen, Si; Bas, Esperanza; Dinh, John; Goncalves, Stefania; Telischi, Fred; Angeli, Simon; Eshraghi, Adrien A.; Van De Water, Thomas
Abstract : Hypothesis: Dexamethasone (DXM) protects against cisplatin-induced auditory hair cell (HC) loss in rat organ of Corti (OC) explants in vitro by reducing levels of oxidative stress and NADPH-Oxidase-3 (NOX-3). Background: Intratympanic DXM has demonstrated protective effects against cisplatin-induced hearing loss in a few animal studies and one clinical trial. However, levels of protection with intratympanic DXM vary significantly between studies, which may not be a result of the intrinsic properties of DXM but rather reflect the diffusion of DXM into the cochlea. The molecular mechanisms and degree of DXM protection against cisplatin ototoxicity are currently unknown. Methods: OC explants from 3-day-old rats were cultured with no treatment or various concentrations of cisplatin (2, 5, or 10 μM) and DXM (75, 150, or 300 μg/mL) in vitro. HC viability and TUNEL assay were performed after 72 hours in vitro and levels of oxidative stress and NOX-3 were evaluated with confocal microscopy after 48 hours in vitro. Analysis of variance with Tukey's post hoc testing was performed. Results: Cisplatin initiated dose-dependent losses of outer HCs (OHCs) in the basal turns of exposed explants ( p < 0.001). DXM protected against cisplatin (2 μM)-induced OHC loss in a dose-dependent manner with complete protection at 300 μg/mL of DXM ( p < 0.001). DXM (150 μg/mL) significantly reduced levels of oxidative stress, NOX-3, and apoptosis in the basal turn of explants exposed to cisplatin (2 μM). Conclusions: DXM protects against cisplatin-induced loss of OHCs in the basal turn of rat OC explants as demonstrated by reductions in oxidative stress and NOX-3 production and decreased levels of apoptotic cell death.